The effect of Kangaroo Mother Care (KMC) on breast feeding at the time of NICU discharge - C. D., Tharashree; M. R., Shravani; S., Srinivasa (International Journal of Contemporary Pediatrics, 2018)
Background: The WHO has defined KMC as early, continuous, and prolonged skin-to-skin contact between the mother and preterm babies. Exclusive breastfeeding is one of the most important essential components of Kangaroo Mother Care in preterm babies Methods: This a cross sectional study, 265 consecutive premature newborns admitted to neonatal intensive care unit (NICU) between May 2015 and May 2016 in KIMS NICU Hospital in Bengaluru were evaluated. All of candidate mothers were educated for KMC and compared with a CMC group. Results: In this study 159 mothers performed kangaroo mother care (KMC group) versus 106 in conventional method care (CMC group). In KMC group exclusive breast feeding was 99 (65.2%) versus 40 (37.7%), and P = .00 in CMC group, at the time of hospital discharge. Receiving KMC, and gestational age were the only effective factors predicting exclusive breastfeeding. Present result indicated that there was a 2.7 time increase in exclusive breastfeeding by KMC, and also weekly increase in gestational age increased it 0.9 times, but maternal age, birth weight, mode of delivery, and 5-minute Apgar score had no influence. Conclusions: KMC is more effective, and increases exclusive breast feeding successfully. It can be a good substitution for CMC (conventional methods of care). It is a safe, effective, and feasible method of care for LBWI even in the NICU settings.